Didattica per l'educazione o didattica per l'istruzione? Il dilemma dell'educazione contemporanea - Giuliano Franceschini (Firenze University Press, 2022)
Equality and inclusion seem to be the two terms destined to dominate the post-pandemic pedagogical and didactic lexicon, alongside those of competence and learning that instead characterized the neoliberal period of education, from the last decade of the twentieth century to today. In particular, we will focus our attention on the differences between didactics for instruction, oriented to learning outcomes, and didactics for education, aimed instead at the integral development of the person and the community. Subsequently we will try a possible synthesis between the two canons, focusing our attention on the characteristics of an authentically inclusive teaching.